Supercapattery: merit merge of capacitive and Nernstian charge storage mechanisms - Chen, George Zheng (Elsevier B.V., 2020)
Supercapattery is the generic name for hybrids of supercapacitor and rechargeable battery. Batteries store charge via Faradaic processes, involving reversible transfer of localised or zone-delocalised valence electrons. The former is governed by the Nernst equation. The latter leads to pseudocapacitance (or Faradaic capacitance) which may be differentiated from electric double layer capacitance with spectroscopic assistance such as electron spin resonance. Since capacitive storage is the basis of supercapacitors, the combination of capacitive and Nernstian mechanisms has dominated supercapattery research since 2018, covering nanostructured and compounded metal oxides and sulfides, water-in-salt and redox active electrolytes and bipolar stacks of multi-cells. The technical achievements so far, such as specific energy of 270 Wh/kg in aqueous electrolyte, and charging-discharging for over 5000 cycles, benchmark a challenging but promising future of supercapattery.